On Propagation Characteristics of Reconfigurable Surface Wave Platform: Simulation and Experimental Verification - Zhiyuan Chu; Kin-Fai Tong; Kai-Kit Wong; Chan-Byoung Chae; Chi Hou Chan (IEEE Access)
Reconfigurable intelligent surface (RIS) as a smart reflector is revolutionizing research for next-generation wireless communications. In contrast to this is a concept of using RIS as an efficient propagation medium for superiorly low path loss characteristics and excellent flexibility. Motivated by the recent porous surface architecture that facilitates reconfigurable pathways with cavities filled with fluid metal by the mean of microfluidic systems.This paper comprehensively studies the propagation characteristics of different pathway configurations in different lossy dielectric materials on the reconfigurable surface wave platform by utilizing Computer Simulation Technology, a commercial full electromagnetic simulation software package, and then conducts S-parameters experimental verification. By using a porous surface model with dense uniformly cylindrical cavities, this paper also examines the optimal scheme for transitioning between a straight pathway and a 90° bend, while attempting to quantify the additional path loss incurred during the 90° bend. The experimental results confirm the simulation results, showing the effectiveness of the proposed reconfigurable surface wave platform for wideband, low-path-loss, and highly programmable communications. The results provide useful references for researchers in the areas.